2018
DOI: 10.3390/md16060181
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aging Effect of Chitosan Oligosaccharide on d-Galactose-Induced Subacute Aging in Mice

Abstract: Chitosan oligosaccharide (COS), a natural polysaccharide with good antioxidant and anti-inflammatory properties, is the depolymerized product of chitosan possessing various biological activities. The present study was designed to investigate the possible anti-aging effect of COS on the aging model mouse induced by d-galactose (d-gal) and explore the underlying mechanism. In the experiment, 48 male Kunming mice (KM mice) were randomly divided into the normal group, model group, positive group, and low-medium-hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 39 publications
7
54
0
Order By: Relevance
“…After the oxidative senescence of the body, a weak body could lead to weight loss (Kong et al, 2018). This was seen our study, as mice in the model group showed lower BW than that of mice in the normal group, and LPSP-YBJ01 could inhibit BW loss.…”
Section: Discussionsupporting
confidence: 53%
“…After the oxidative senescence of the body, a weak body could lead to weight loss (Kong et al, 2018). This was seen our study, as mice in the model group showed lower BW than that of mice in the normal group, and LPSP-YBJ01 could inhibit BW loss.…”
Section: Discussionsupporting
confidence: 53%
“…(2011) reported that COS protected the adverse effects of lipopolysaccharide on the liver of rats by decreasing the serum ALT and AST level. Kong et al. (2018) also reported that COS inhibited the D-galactose–induced upregulation of the serum ALT and AST level.…”
Section: Discussionmentioning
confidence: 90%
“…30 D-gal is a reducing sugar, which causes the increase in free radicals and induces the oxidative damage, 31 finally leading to the gradual aging and damage of the body similar to those in natural aging. 32,33 It has been reported that in the aging host, the levels of cytokines also change, and they play an important regulatory role in the immune system. 34,35 In the current study, we found that Anwulignan increased the serum levels of IL-2, IL-4, and IFN-γ in the aging mice, while it decreased the serum levels of IL-6 and TNF-α, suggesting that Anwulignan can restore the immune function that is declined in the process of aging by regulating the level of the cytokines in mice and reversing the inflamm-aging process.…”
Section: Discussionmentioning
confidence: 99%